2016
DOI: 10.1371/journal.pone.0167375
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove Crab Ucides cordatus Removal Does Not Affect Sediment Parameters and Stipule Production in a One Year Experiment in Northern Brazil

Abstract: Mangrove crabs influence ecosystem processes through bioturbation and/or litter feeding. In Brazilian mangroves, the abundant and commercially important crab Ucides cordatus is the main faunal modifier of microtopography establishing up to 2 m deep burrows. They process more than 70% of the leaf litter and propagule production, thus promoting microbial degradation of detritus and benefiting microbe-feeding fiddler crabs. The accelerated nutrient turn-over and increased sediment oxygenation mediated by U. corda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The result corroborates the findings of Pülmanns et al (2015) in the rainy season, when sediment salinity in "rooted" areas was also higher than in "gap" areas (27 and 31 in gap areas and rooted areas, respectively, at the end of the rainy season) Findings by Smith III (1987), demonstrating a salinity of 57.5 in areas with high amounts of aerial roots versus 55.2 in gaps, are also in concordance with the present results. A microcosm experiment by Pülmanns et al (2016), showed lower salinity in treatments with (41) than without (47) artificial burrows after 6 months (both treatments started with sediment salinity of 37.5 at the first centimeter),…”
Section: Discussionmentioning
confidence: 99%
“…The result corroborates the findings of Pülmanns et al (2015) in the rainy season, when sediment salinity in "rooted" areas was also higher than in "gap" areas (27 and 31 in gap areas and rooted areas, respectively, at the end of the rainy season) Findings by Smith III (1987), demonstrating a salinity of 57.5 in areas with high amounts of aerial roots versus 55.2 in gaps, are also in concordance with the present results. A microcosm experiment by Pülmanns et al (2016), showed lower salinity in treatments with (41) than without (47) artificial burrows after 6 months (both treatments started with sediment salinity of 37.5 at the first centimeter),…”
Section: Discussionmentioning
confidence: 99%
“…This decapod crustacean is also considered a key species for the ecological balance within benthic communities of mangrove forests, and have the largest biomass among mangrove invertebrates ( Wolff, Koch & Isaac, 2000 ). The species has a strong impact on litter turnover, nutrients cycling, soil aeration and forest productivity ( Pülmanns et al, 2014 , 2016 ). Despite its importance to the ecosystem and abundance throughout the year, U. cordatus is currently on the Brazilian list of species threatened by overfishing ( Pinheiro & Rodrigues, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, we are also aware that our findings need to be corroborate by other field observations and trials. In particular, we recognise the importance of performing manipulative removal or exclusion experiments as historically done in other intertidal habitats [83], despite such an approach is very difficult or even impossible to be applied in mangroves with large sesarmid crabs [84, 85]. Finally, this study adds interference competition for food as a key factor in the complex interplay of biotic (predation, competition for space) and abiotic environmental factors determining the spatial and distribution patterns of mangrove fauna.…”
Section: Discussionmentioning
confidence: 99%